Melayu Islam Beraja : Ideologi Negara Brunei Darussalam - Ahmad Effendi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
Abstract This paper is about the Malay Islamic Monarchy as the ideology of the Brunei Darussalam state which has been proclaimed at the independence day of Brunei on January 1, 1984 AD. The Malay Islamic Monarchy as a continuity of the struggle of the kings and people of Brunei Darussalam in preserving culture, religion and government system. The Malay Islamic Monarchy as the ideology of the state is an independent, sovereign and democratic state. Independence is a right for every nation and state. It was not coincidence, but was born trough a long historical process starting form Awang Alak Betatar convert Islam and continued by the king until now. The Malay Islam Monarchy also as identity and worldview of the people of Brunei Darussalam which is practicing Malay as culture and customs, understanding Islam as a complete and perfect religion, and recognizing the king as the highest leader and absolute power in the state of Brunei Darussalam. The position of Islam in this country also provides an important role for peace and prosperity, so Islam becomes the core of the Malay Islam Monarchy itself. Kata Kunci ; Melayu Islam Beraja